Impact of the Guard Rings on Self-Induced Signal and Leakage Current in Trench-Isolated Low Gain Avalanche Diodes - Gordana Lastovicka-Medin; Gregor Kramberger; Jiri Kroll; Mateusz Rebarz (Sensors)
In this contribution, we explored the interplay of guard ring (GR) configuration and isolation structures, as well as irradiation effects, which all together create a rich landscape of phenomena such as self-induced signals (“ghosts”) in trench-isolated Low-Gain Avalanche Diodes (TI-LGADs). The ghost effect is related to the increased surface current due to presence of SiO2 trenches (and defects) in studied diodes, but it is also affected by interplay between the guard ring(s) and the n+ bias ring, implanted in inter-pixel region of these devices. In double-trenched sensors, the n+ bias ring is inserted in between the two trenches. We present the investigation on the role of these structures on the self-induced signals in trench-isolated sensors from two different productions (RD50 and AIDAinnova). The sensors from the first production have multiple guard rings, whereas the second type of devices feature only one. Detailed examination of the ghost effect and leak current was performed when guard rings were left floating or connected to the pixels (brought to the same potential). The results show that guard ring configuration in trenched sensors can be critical for the leak current and the presence of a ghost signal. To our best knowledge, the latter problem has not been investigated yet.